Discontinuous FRP-Confinement of Masonry Columns - Cascardi, Alessio; Lerna, Michela; Micelli, Francesco; Aiello, Maria Antonietta (Frontiers in Built Environment, 2020)
Recent seismic events, all over the world, demonstrated that masonry constructions are prone to brittle collapses when shear or compression capacity is reached. It is clear that, in many real cases, masonry columns need to be strengthened for enhancing their load-carrying capacity and to develop a more ductile response. The Fiber Reinforced Polymers (FRPs) confinement of masonry columns is a well-known technique that may produce these advantages. Unfortunately, full-wrapping insulates the column from the environment; so interstitial humidity can easily occur and cause the acceleration of the masonry’s decay. In order to prevent it, partial-confinement is commonly assessed instead of total-jacketing. For this reason, a research was led, consisting of an experimental and theoretical study focused on the discontinuous FRP-confinement. Thus, two different series of masonry columns were confined with Glass-FRP (GFRP) and Carbon-FRP (CFRP) strips bonded to the column with an epoxy resin. Different schemes of FRP-wrapping were investigated by means of uniaxial compression tests. Moreover, an analytical method for the prediction of the experimental results was also provided. The proposed model was based on the relationship between the different lateral deformations of the confined and unconfined regions (experimentally recorded by using strain gauges). The new iterative procedure was found able to provide theoretical stress vs strain curves; which demonstrated to accurately match the experimental recordings. The proposed model was also validated by parametric analyses, presented in the paper.